2012
DOI: 10.1167/iovs.11-9130
|View full text |Cite
|
Sign up to set email alerts
|

Thickness, Phase Retardation, Birefringence, and Reflectance of the Retinal Nerve Fiber Layer in Normal and Glaucomatous Non-Human Primates

Abstract: PURPOSE. We identified candidate optical coherence tomography (OCT) markers for early glaucoma diagnosis. Time variation of retinal nerve fiber layer (RNFL) thickness, phase retardation, birefringence, and reflectance using polarization sensitive optical coherence tomography (PS-OCT) were measured in three non-human primates with induced glaucoma in one eye. We characterized time variation of RNFL thickness, phase retardation, birefringence, and reflectance with elevated intraocular pressure (IOP). METHODS.One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 28 publications
0
51
0
Order By: Relevance
“…Recent studies have shown that a decrease in RNFL reflectance occurs prior to thinning of the RNFL [5][6][7][8][9][10][11], and suggest that direct OCT measurement of RNFL reflectance may provide a powerful new method for the early detection of glaucoma. Although directional reflectance is a major source of variability for RNFL reflectance measurements [24][25][26], none of the in vivo studies took this into account.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have shown that a decrease in RNFL reflectance occurs prior to thinning of the RNFL [5][6][7][8][9][10][11], and suggest that direct OCT measurement of RNFL reflectance may provide a powerful new method for the early detection of glaucoma. Although directional reflectance is a major source of variability for RNFL reflectance measurements [24][25][26], none of the in vivo studies took this into account.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Optical Coherence Tomography (OCT), which is widely used in clinical diagnosis of glaucoma, measures RNFL thickness by identifying the RNFL as a highly reflective layer under the retinal surface, with change of thickness used as a biomarker for axonal damage [1][2][3][4]. Recent studies of glaucomatous retinas reveal that a decrease of RNFL reflectance occurs prior to thinning of the RNFL [5][6][7][8][9][10][11]. Glaucoma damages retinal ganglion cells (RGC) and their axons [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar analysis was followed by Yamanari et al [10]. Kemp et al and Dwelle et al fitted RNFL DPPR data in the Poincaré sphere [11,12]. Using an open air PS-OCT system without single mode fiber and an input state that was circularly polarized, Götzinger et al determined the birefringence induced by the RNFL by fitting DPPR data with a linear regression method [13].…”
Section: Introductionmentioning
confidence: 97%